2011
DOI: 10.5251/abjna.2011.2.4.698.707
|View full text |Cite
|
Sign up to set email alerts
|

Diallel analysis of cowpea (Vigna unguiculata (L.) Walp.) for some physical properties of seed under the Sudano-guinean conditions

Abstract: The present study was undertaken at Dang (soudano-guinean zone of Cameroon) to determine the variability of 100-seed weight, geometric surface, porosity and sphericity of the seeds of 10 cowpea (Vigna unguiculata) genotypes and investigate the genetic basis of these characters through a 5x5 half-diallel cross mating. Knowledge of the physical properties of the seed of cowpea was necessary for the design of equipment for transporting, sorting, cleaning, separating, smashing and processing it into different food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…The role of both additive and non-additive gene action in the inheritance of yield and its components traits have also been reported by many other workers in blackgram (Singh and Singh, 2005;Karthikeyan, et al 2007;Bhagirath, et al 2009;Chakraborty, et al 2010;Panigrahi, et al 2015;Vadivel, et al 2019), greengram (Singh, et al 2007;Patil, et al 2011;Thangavel and Thirugnanakumar, 2011;Singh et al, 2016) and cowpea (Egbadzor et al, 2013;Dias et al, 2016). The substantial presence of non-allelic interactions has also been reported by Gupta (2005), Khan et al (2004), Chand (2000, Adeyanju et al (2012), Ramakant and Srivastava (2012) and Bindra et al (2017) in backgram; Thangavel and Thirugnanakumar (2011) and Singh et al (2016) in mungbean; and Tchiagam et al (2011) in cowpea. However, contrary to our findings absence of epistasis has also been reported by Rehman et al (2009) in mungbean for seed yield.…”
Section: Resultsmentioning
confidence: 78%
“…The role of both additive and non-additive gene action in the inheritance of yield and its components traits have also been reported by many other workers in blackgram (Singh and Singh, 2005;Karthikeyan, et al 2007;Bhagirath, et al 2009;Chakraborty, et al 2010;Panigrahi, et al 2015;Vadivel, et al 2019), greengram (Singh, et al 2007;Patil, et al 2011;Thangavel and Thirugnanakumar, 2011;Singh et al, 2016) and cowpea (Egbadzor et al, 2013;Dias et al, 2016). The substantial presence of non-allelic interactions has also been reported by Gupta (2005), Khan et al (2004), Chand (2000, Adeyanju et al (2012), Ramakant and Srivastava (2012) and Bindra et al (2017) in backgram; Thangavel and Thirugnanakumar (2011) and Singh et al (2016) in mungbean; and Tchiagam et al (2011) in cowpea. However, contrary to our findings absence of epistasis has also been reported by Rehman et al (2009) in mungbean for seed yield.…”
Section: Resultsmentioning
confidence: 78%
“…Cowpea is planted on loamy, sandy, sandy-clay soils, and yields vary based on soil texture. On sandy clay soil in Cameroon, Tchiagam et al (2010) reported 892 kg ha −1 and 1369 kg ha −1 as grain and fodder yields, respectively. Similarly, on loamy soil, Ewansiha et al (2017) found average grain and fodder yields of 1260 kg ha −1 and 2446 kg ha −1 , respectively in Nigeria.…”
Section: Dual-purpose Varietiesmentioning
confidence: 99%
“…Hal ini juga didukung oleh penelitian pada benih padi yang dilakukan oleh Akram et al (2007) dan benih cowpea (Vigna unguiculata (L.) Walp.) yang dilakukan oleh Tchiagam et al (2011).…”
Section: Analisis Daya Gabungunclassified